Mercury concentrations in feathers of marine birds in Arctic Canada. Issue 1 (15th September 2015) - Mallory, Mark L.; Braune, Birgit M.; Provencher, Jennifer F.; Callaghan, D. Benjamin; Gilchrist, H. Grant; Edmonds, Samuel T.; Allard, Karel; O'Driscoll, Nelson J.
Highlights: Total and methylmercury were sampled in feathers of Canadian Arctic marine birds. Species in higher trophic positions had higher mercury concentrations. Ivory gulls had exceptionally high mercury, especially in primary feathers. The proportion of mercury as methylmercury in feathers varied across species. Abstract: Mercury (Hg) concentrations are a concern in the Canadian Arctic, because they are relatively high compared to background levels and to similar species farther south, and are increasing in many wildlife species. Among marine birds breeding in the Canadian Arctic, Hg concentrations have been monitored regularly in eggs and intermittently in livers, but feathers have generally not been used as an indicator of Hg exposure or burden. We examined Hg concentrations in six marine bird species in the Canadian Arctic. Ivory gull Pagophila eburnea, feather Hg was exceptionally high, while glaucous gull Larus hyperboreus feather Hg was unexpectedly low, and ratios of feather THg to egg THg varied across species. The proportion of total Hg that was comprised of methyl Hg in ivory gull feathers was lower than in other species, and may be related to photo-demethylation or keratin breakdown in semi-opaque feather tissue.